138k views
0 votes
What is the first step in solving this system of equations? 2x – 5y = 7 3x + 7y = –3

2 Answers

4 votes
Multiplying equation by-
2x-5y=1....[*3]
-3x+7y=-3..[*2]


Adding both equations after multiplication,we get-
6x - 15y = 3
-6x + 14y =-6

-------------
y = -3
-------------
User Yinglin
by
6.9k points
3 votes
The first step will be to multiply the equation 2x -5y =7 by -3 and multiply the equation 3x + 7y = -3 by 2.
Your new equations will be -6x + 15y = -21.
6x + 14y = -6
User Tommo
by
8.0k points